2014
DOI: 10.1038/nature13858
|View full text |Cite
|
Sign up to set email alerts
|

The ‘mitoflash’ probe cpYFP does not respond to superoxide

Abstract: Ageing and lifespan of organisms are determined by complicated interactions between their genetics and the environment, but the cellular mechanisms remain controversial. There have been a number of studies suggesting that cellular energy metabolism and free radical dynamics affect lifespan, implicating mitochondrial function. Recently, Shen et al.1 provided apparent mechanistic insight by reporting that mitochondrial oscillations of ‘free radical production’, called ‘mitoflashes’, in the pharynx of 3-day old C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 17 publications
4
103
0
Order By: Relevance
“…However, their chemical specificity in mitochondria also remains a concern. For example, cpYFP that was reported as responsive to superoxide and has been used as such also in plant mitochondria (He et al, 2012) has been conclusively shown not to react to superoxide, but to pH changes (Schwarzländer et al, 2014), while the H 2 O 2 -responsive HyPer family of fluorescent protein probes (Costa et al, 2010) also suffer from pH artifacts, making measurements problematic in the matrix where pH can change rapidly (Schwarzländer et al, 2012b). Dynamic measurements using such probes also rely on efficient probe regeneration after oxidation via the endogenous glutathione/glutaredoxin system.…”
Section: Measuring Mtros In Vitro and In Vivomentioning
confidence: 99%
“…However, their chemical specificity in mitochondria also remains a concern. For example, cpYFP that was reported as responsive to superoxide and has been used as such also in plant mitochondria (He et al, 2012) has been conclusively shown not to react to superoxide, but to pH changes (Schwarzländer et al, 2014), while the H 2 O 2 -responsive HyPer family of fluorescent protein probes (Costa et al, 2010) also suffer from pH artifacts, making measurements problematic in the matrix where pH can change rapidly (Schwarzländer et al, 2012b). Dynamic measurements using such probes also rely on efficient probe regeneration after oxidation via the endogenous glutathione/glutaredoxin system.…”
Section: Measuring Mtros In Vitro and In Vivomentioning
confidence: 99%
“…The authors proposed that both hormones act as mitochondrial signals through ROS formation. Those conclusions will require future reassessment because the employed ROS-detection methodology based on the cpYFP sensor protein has since proven inappropriate (Schwarzländer et al, 2014;Demaurex and Schwarzländer, 2016). A potential link between mitochondrial ROS and auxin is independently supported by Arabidopsis plants lacking the mitochondrial FTSH4 AAA-protease that is required for the assembly and/or stability of complex I and, even more, complex V. Similar to abo6 mutants, auxin accumulation or responsiveness was reduced in these plants, and external application of auxin could revert the phenotypic symptoms of ftsh4 mutant plants .…”
Section: Auxinmentioning
confidence: 99%
“…Since then, other groups have also used this probe and other probes and detected similar bursting single mitochondrial events, which are associated with mitochondrial ROS production and redox signaling and play critical roles in cell physiology and pathology (10,40,45,55,57). However, concerns over the pH and superoxide sensitivity of the cpYFP probe have also been raised, which suggested that the bursting flash events detected by cpYFP could be interpreted as transient alkalization signals in mitochondrial matrix, named pH flashes (41,43,44). This controversy could arise from the differences in in vitro calibration of cpYFP and will need to be resolved most likely with the elucidation of crystal structure of cpYFP (14,44).…”
mentioning
confidence: 99%